Study of a division-like property - Khanfir, Robin; Seguin, Beranger Fabrice (Journal of Algebra and Its Applications)
We study a weak divisibility property for noncommutative rings: a nontrivial ring is fadelian if for all nonzero a and x there exist b, c such that x=ab+ca. We prove properties of fadelian rings and construct examples thereof which are not division rings, as well as non-Noetherian and non-Ore examples.

"German Dream" - German Nightmare: Paradoxien der postmigrantischen Gesellschaft in Burhan Qurbanis "Berlin Alexanderplatz" - Morrien, Rita (Postmigrantische Literatur. Grundlagen, Analysen, Positionen)
Burhan Qurbani gelingt mit seiner freien Adaption von Döblins "Berlin Alexanderplatz" (2020) der Spagat, einerseits eine radikale Aktualisierung der Geschichte des Franz Biberkopf vorzulegen, indem er einen Schwarzen Geflüchteten zum Protagonisten des Films macht, und sich andererseits an der thematischen Essenz des Romans wie auch an der komplexen Montagetechnik Döblins zu orientieren. Über eine die Struktur des gesamten Films prägende Ästhetik des Traums werden nicht nur die traumatischen Prägungen eines auf der Flucht schuldig gewordenen Heimatlosen, sondern auch die Widersprüche einer postmigrantischen Gesellschaft gestaltet, die nach Naika Foroutan dem Anspruch, eine plurale Demokratie zu sein, nicht ohne tiefreichende Ambivalenzen begegnet. Der Film funktioniert als ‚Dream Screen‘, auf dem sich kollektive Ängste vor dem Verlust weißer Privilegien und ein postkoloniales Begehren (Struck und Bay), das gleichermaßen durch Vereinnahmung und aggressive Abwehr des Anderen gekennzeichnet ist, vermengen.
Keywords: postmigrantische Gesellschaft; filmische Adaption; "Berlin Alexanderplatz"; Traumästhetik; postkoloniales Begehren

Investigation on the load-bearing capacity and joint formation of hybrid functional components joined by orbital forming - Hetzel, A.; Wituschek, S.; Römisch, D.; Sippel, F.; Lechner, M.; Merklein, M. (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Increasing material costs, decreasing availability, and ever-higher demands on environmental compatibility and complexity require new strategies in the development and production of functional components. Consequently, a combined approach from the areas of design, material science, and manufacturing is mandatory, in order to meet the requirements. Reducing the number of parts, using lightweight materials and applying hybrid components with a multimaterial mix are possible solutions. Nevertheless, conventional joining operations like welding or riveting are reaching their limits in terms of material utilization, load-bearing capacity as well as versatility of the process. Thus, innovative and versatile joining by forming operations and process combinations are focus of current research. In this context, the innovative process of orbital forming had been investigated as a joining by forming operation to manufacture load-adapted hybrid functional components. By tilting of one tool component during the process, a radial material flow is generated, allowing the crimping of the two joining partners. Nevertheless, the load-bearing capacity in axial direction could be identified as limiting factor for a possible application. Therefore, the aim of this investigation is the development of a fundamental process understanding on the influence of a novel geometrical adaption of the joint on the resulting load bearing capacity. The influence of varying geometrical proportions of the joint on the quality is evaluated, considering the form filling, the geometrical properties of the components as well as the maximum transmittable axial load. As joining partners, the dual-phase steel DP600 and the aluminum alloy EN AW-5754 with a thickness of 2.0 mm are used.

Changes in partner models – Effects of adaptivity in the course of explanations - Buhl, Heike M.; Fisher, Josephine Beryl; Rohlfing, Katharina (Proceedings of the Annual Meeting of the Cognitive Science Society)

The use of IT and OER to support remote sustainable work in Europeans Green Economy - Beutner, Marc; Schneider, Jennifer Nicole (Procedia Computer Science)

Medienarchäologie des Wohnens. Mediengeschichtliche Methode zum Zusammenhang von Medien und Wohnen - Miggelbrink, Monique (Wohnen erforschen. Qualitative Methoden und forschungspraktische Reflexionen)

Datengetriebene Modellbildung für nichtlineare mechatronische Systeme in regelungstechnisch verwertbarer Form - Junker, Annika
Der modellbasierte Regelungsentwurf erfordert eine möglichst genaue Kenntnis über das dynamische Verhalten des zugrunde liegenden physikalischen Systems. Durch maschinelle Lernverfahren besteht das Potenzial den Modellierungsaufwand im Vergleich zum klassischen Vorgehen zu reduzieren, indem physikalisches Vorwissen und an Messdaten trainierte Modelle effektiv zusammengeführt werden. Diese Dissertation entwickelt Methoden zur datengetriebenen Bestimmung von Modellen für den Regelungsentwurf nichtlinearer mechatronischer Systeme. Dazu wird die regelungstechnische Anwendbarkeit von Koopman-Operator-basierten Verfahren analysiert, die nichtlineare Dynamiken durch lineare Modelle approximieren. Darüber hinaus wird ein neuartiges Verfahren zur datengetriebenen Bestimmung von Port-Hamilton-Modellen entwickelt, die Energiezusammenhänge plausibel abbilden und sich unmittelbar für einen passivitätsbasierten Regelungsentwurf verwenden lassen. Zudem werden Ansätze zur automatischen Aktualisierung des im Regelkreis verwendeten Streckenmodells bei Modellunsicherheiten oder auftretenden Veränderungen der Systemdynamik vorgestellt. Experimentelle sowie simulative Untersuchungen demonstrieren die herausragende Prädiktionsgenauigkeit der datengetriebenen Modelle und die hohe Regelgüte. Die Ergebnisse dieser Dissertation leisten einen bedeutenden Beitrag, weil die datengetriebenen Modelle eine aus regelungstechnischer Sicht verwertbare Form aufweisen. Sie sind physikalisch interpretierbar und lassen sich nahtlos in bestehende Analyse- und Entwurfsmethoden einbinden. Dies eröffnet neue Perspektiven für zukünftige Anwendungen und Weiterentwicklungen.

Spin-Dependent Exciton–Exciton Interactions in a Mixed Lead Halide Perovskite Crystal - Grisard, Stefan; Trifonov, Artur V.; Hahn, Thilo; Kuhn, Tilmann; Hordiichuk, Oleh; Kovalenko, Maksym V.; Yakovlev, Dmitri R.; Bayer, Manfred; Akimov, Ilya A. (ACS Photonics)

Aus Reflexion in Unmittelbarkeit. Herders Bückeburger Geschichtsphilosophie - Süßmann, Johannes (Johann Gottfried Herder. Die Formation seines Werkes in Bückeburg 1771–1776)

The Effects of Norms on Environmental Behavior - Dannenberg, Astrid; Gutsche, Gunnar; Batzke, Marlene C. L.; Christens, Sven; Engler, Daniel; Mankat, Fabian; Möller, Sophia; Weingärtner, Eva; Ernst, Andreas; Lumkowsky, Marcel; von Wangenheim, Georg; Hornung, Gerrit; et al. (Review of Environmental Economics and Policy)

Vergleichsprozesse und ihr Einfluss auf die selbst wahrgenommenen Fähigkeiten angehender gewerblich-technischer Lehrkräfte - Vernholz, Mats; Temmen, Katrin (Book of Abstracts zum 8. Technikdidaktik-Symposium)

Im Spannungsfeld zwischen Fach- und Bildungswissenschaft - Einflussfaktoren auf die Selbsteinschätzungen gewerblich-technischer Lehramtsstudierender in den verschiedenen Bereichen des Master of Education - Vernholz, Mats; Temmen, Katrin

Uni trifft Schule - Kooperative Unterrichtsentwicklung unter Einbezug von KI in der gewerblich-technischen Lehramtsausbildung - Vernholz, Mats; Schäfers, Johannes; Jonas-Ahrend, Gabriela; Temmen, Katrin

Implikationen von Künstlicher Intelligenz für die Aus- und Fortbildung von Lehrpersonen - Aufenanger, Stefan; Lehberger, Regine; Nicolas, Michael (Medien – Bildung – Forschung. Integrative und interdisziplinäre Perspektiven)
Der Band versammelt Beiträge aus der Erziehungswissenschaft, verschiedenen Fachdidaktiken und der Psychologie zu theoretischen und forschungsmethodischen Perspektiven zur Medienbildung, Medienbildung in Schule und Elternhaus sowie medienpädagogischer Professionalisierung im Rahmen der Lehrkräftebildung und in der Arbeitswelt. Als Phänomene werden u.a. Künstliche Intelligenz, Open Educational Practices und Spielfilme aufgegriffen. Es werden sowohl grundlagentheoretische Überlegungen als auch Ergebnisse empirischer Projekte präsentiert. Dabei werden Medienbildungsprozesse in formalen sowie informellen Kontexten fokussiert. Festschrift für Bardo Herzig. (DIPF/Orig.)

Netzwerk empirische Forschung zur beruflichen Lehrkräftebildung (Poster) - Jonas-Ahrend, Gabriela; Kaiser, Franz; Traum, Anne

The Emergence of an Invisible College as an Offshoot withn the ISATT Community - Ratnam, Tara; Gudjonsdottir, Hafdis; Jonas-Ahrend, Gabriela

Model-based planning of test cases and test scenarios to support engineering of Cyber-Physical Systems - Gräßler, Iris; Ebel, Marcel; Pottebaum, Jens (2024 IEEE International Symposium on Systems Engineering (ISSE))
Engineering methodologies for Cyber-Physical Systems (CPS) call for planning simulations and physical testing in early phases of product creation. Even in Model-Based Systems Engineering, there is a lack of systematic support that results in avoidable costs and iterations in the engineering process. Planning test cases and test scenarios along the product engineering process is not sufficiently integrated in terms of support especially for verification and validation engineers. Based on a systematic literature review, concepts for model-based planning of testing are developed. Characteristics of test cases and test scenarios of CPS are systematically identified. Generic templates for the creation of test cases and scenarios are derived. Based on the templates, a System Modeling Language (SysML) profile extension is developed which enables intuitive modelling of test cases and scenarios. The SysML profile is evaluated in a sample System-of-Systems in Disaster Response. It subsumes various types of sensor systems like rescue robotics, data science algorithms and visualization technologies like Augmented Reality to support decisions in extreme weather events. The templates and SysML profile significantly add value for engineers in the early and systematic planning of verification and validation.
Keywords: Systems Engineering; Systems verification; System testing

Leibniz, Gottfried Wilhelm, General Inquiries on the Analysis of Notions and Truths, edited with an English translation by Massimo Mugnai, Oxford University Press: Oxford 2021 (BSHP New Texts in the History of Philosophy) - Peckhaus, Volker (Mathematical Reviews, MR457231)

Fraenkel, Adolf Abraham Halevi - Peckhaus, Volker (NDB-online, veröffentlicht am 01.07.2024)

Knowledge Transfer for Microgrids Sustainability – the Case of East Africa - Bogere, Paul